Nitrogen-doped porous carbon fiber/vertical graphene as an efficient polysulfide conversion catalyst for high-performance lithium–sulfur batteries. Issue 2 (30th November 2021) - Lin, Junsheng; Mo, Yangcheng; Li, Shiwen; Yu, Jie
Abstract : A freestanding sulfur cathode based on nitrogen-doped porous carbon fiber/vertical graphene (NF@VG) composites is proposed to effectively boosts the catalytic conversion kinetics of polysulfides and inhibit the shuttle effect of polysulfides. Abstract : Under high sulfur loading, high sulfur content and low electrolyte/sulfur ratio (E/S), the practical application of lithium–sulfur (Li–S) batteries are seriously limited by the negative and slow kinetics of polysulfide. Here, a freestanding sulfur cathode based on nitrogen-doped porous carbon fiber/vertical graphene (NF@VG) composites is proposed. The porous structure and nitrogen doping effectively enhance absorption of polysulfides through physical confinement and chemical action, while vertical graphene network greatly promotes electron transfer and boosts the catalytic conversion kinetics of polysulfides. Therefore, the as-prepared sulfur cathode exhibits an initial capacity of 738 mA h g −1, and a maintained capacity of 609 mA h g −1 after 600 cycles with only 0.029% capacity fading per cycle at 1C rate at a sulfur loading of 7 mg cm −2 . In addition, the battery displays an areal capacity of 12.8 mA h cm −2 under high sulfur loading (13 mg cm −2 ), high sulfur content (81.6 wt%), and low E/S (4.8 μL mg −1 ), indicating that NF@VG composite fibers are highly competitive as a sulfur host for Li–S batteries.